A fair share of village water [Blog post] - Elias, Marlène (2019)
Scarce water resources in developing countries are under pressure from climate change, with droughts and extreme weather events particularly impacting rural communities that depend on farming for their survival. Living on this knife edge means that water resources become ever more precious, with a clear potential for conflicts between farmers and other water users.